Globalization and the Sociolinguistic Challenge of the 21st Century Critical Pedagogy: A Case for Language/Culture Minority Students - Jamil Asghar; Khurram Shehzad (NUST Journal of Social Sciences and Humanities, 2021)
In spite of the fact that ours is a world of immigration, deepening ethnic textures, globalization, transnational histories, ethnolinguistic diversity, socioecono-mic rivalries, and intercultural complexities, the role and significance of bilingual and multicultural education are far from being adequately realized. These demographic imperatives and a host of other cross-cultural and transnational praxis are bringing about a growing percentage of students who speak a first language other than English. All over the world, classrooms are experiencing a radical transformation due to an unparalleled intercultural diversity which is spreading its tentacles all across the globe including Pakistan which, of late hit by the CPEC spectacle, is likely to experience an unprecedented influx of foreign students. These are paradigm shifting questions and call for a radical re-conceptualization not just of classrooms but also of the entire pedagogic space and curricular habitus. The paper makes a coherent appraisal of these questions and advances a plea for the greater inclusion of a broad-based, bilingual, and multicultural education by laying down key guidelines for teachers, administrators, policy-makers, educators, and parents at large.